The Effect of Temperature on the Living Conditions of Collembola - Odilovna, Atoyeva Dilsora (PT. Antis International Publisher, 2024)
The dynamics of the composition and proportions of soil invertebrates helps to think about the direction of the processes of soil formation and the disturbance of the environmental regime. A large number of important results have been obtained in this direction. Information was collected on the system of zoological indication of the age of primitive soils, stages of decomposition of organic residues in composts, elementary soil processes, stages of community formation in industrial waste, stages of wood decomposition, levels of soil degradation in recreational areas, pollution with oil products.